ANALISIS PENGGUNAAN MEDIA WAYGROUND SEBAGAI EVALUASI UJIAN TENGAH SEMESTER (UTS) DI SEKOLAH MENENGAH KEJURUAN MUHAMMADIYAH SALAWATI : AN ANALYSIS OF THE USE OF WAYGROUND AS A TOOL FOR MID-SEMESTER EXAM EVALUATION AT MUHAMMADIYAH SALAWATI VOCATIONAL HIGH SCHOOL - kiki hndayani; Kiki Handayani (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
This study aims to analyze the use of Wayground as an evaluation medium in the Midterm Examination (UTS) at SMK Muhammadiyah Salawati. The approach used is qualitative descriptive with data collection through documentation, observations, and interviews. The study involved 1 teachers and 30 students from the Computer and Network Engineering department. The findings of the study reveal that the use of Wayground successfully increased student engagement and motivation during exams, while also making it easier for teachers to create questions and carry out assessments efficiently. The platform provides automatic feedback that accelerates the evaluation process. However, technical challenges such as internet connectivity stability and students’ device readiness remain obstacles that need to be addressed. Overall, the use of Wayground has proven effective in improving efficiency and interactivity during evaluations, although improvements in technical infrastructure are still required.